Evaluation of a DBT group within adolescent residential care - Katie McIntyre (Scottish Journal of Residential Child Care)
Dialectical behavioural therapy (DBT) is an evidence-based cognitive behavioural intervention which has been shown to aid difficulties such as interpersonal relationships, emotion regulation and distress tolerance in women with personality disorder or displaying self-harm and suicidal behaviours. There is growing evidence that DBT can be utilised with adolescent populations also exhibiting such behaviours. The following evaluation looks at a DBT skills group implemented with young females in a Scottish residential service. Semi-structured interviews with young people and focus groups with staff were completed and transcribed. Thematic analysis was used to draw out key themes and these are discussed in relation to implementation for future practice.